2021
DOI: 10.1308/rcsann.2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Tracheomalacia after thyroidectomy for retrosternal goitres requiring sternotomy– a myth or reality?

Abstract: Introduction Tracheomalacia after thyroidectomy is not well understood. Reports on tracheomalacia are conflicting, with some suggesting a high rate and other large cohorts in which no tracheomalacia is reported. The aim of our study was to assess the incidence and factors associated with tracheomalacia after thyroidectomy in patients with retrosternal goitres requiring sternotomy at a high-volume tertiary care referral centre. Methods A longitudinal cohort study was conducted from January 2011 to December 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Tracheomalacia remains the most dreadful complication in the case of large RGs, despite its incidence seems to be very low 92 . In a series of 40 patients subjected to thyroidectomy with sternotomy, tracheomalacia was reported in 3 cases, in absence of any patient-or thyroid-related factor significantly associated with its development: one patient required tracheal resection with anastomosis, and two patients required tracheostomy 92 .…”
Section: Complications Associated With Surgery For Rgmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracheomalacia remains the most dreadful complication in the case of large RGs, despite its incidence seems to be very low 92 . In a series of 40 patients subjected to thyroidectomy with sternotomy, tracheomalacia was reported in 3 cases, in absence of any patient-or thyroid-related factor significantly associated with its development: one patient required tracheal resection with anastomosis, and two patients required tracheostomy 92 .…”
Section: Complications Associated With Surgery For Rgmentioning
confidence: 99%
“…Tracheomalacia remains the most dreadful complication in the case of large RGs, despite its incidence seems to be very low 92 . In a series of 40 patients subjected to thyroidectomy with sternotomy, tracheomalacia was reported in 3 cases, in absence of any patient-or thyroid-related factor significantly associated with its development: one patient required tracheal resection with anastomosis, and two patients required tracheostomy 92 . In another paper, 17 cases of tracheomalacia out of 106 cases were reported, probably caused by long-standing tracheal compression from RG: this study suggested that prolonged intubation was sufficient to resolve airways collapse without tracheal reconstruction in all cases 93 .…”
Section: Complications Associated With Surgery For Rgmentioning
confidence: 99%
“…When patients with SG are extubated, those who develop respiratory distress can generally be reintubated without a problem. [ 2 , 7 , 70 ] Tracheostomy can be considered in patients who have problems in reintubation and who continue to have respiratory distress. Agarwal et al suggested that it may contribute to the early healing of tracheomalacia by causing fibrosis in the soft tissue around the tracheostomy in patients with tracheomalacia.…”
Section: Tracheomalaciamentioning
confidence: 99%
“…In the treatment of tracheomalacia, besides intubation and tracheostomy, treatment alternatives such as surgical tracheopexy methods, tracheal stents, surgical external stabilization, and tracheal resection are recommended. [ 2 , 7 , 70 ]…”
Section: Tracheomalaciamentioning
confidence: 99%